Informe sobre el Congreso Mundial de Bioética. (Beijing 2006) - Navarro Aranguren, Marysa (Huarte de San Juan. Geografía e Historia, 2006)
Bioethics is a multidisciplinary field that developed in the late Sixties as a consequence of the challenge presented by new technologies. It involves philosophers, social scientists, scientists, lawyers, policy makers, as well as activitists. Its worldwide association meets every two years and in August 2006, it met in Beijing, China.